Root esthetic score (RES) comparisons of FGG and PE-FGG procedures in Miller class II and III recessions in mandibular anterior teeth - Hatice Balci Yuce (Cumhuriyet University, 2015)
Objective: Free gingival graft (FGG) is frequently chosen for the treatment of recessions in mandible. Mandibular anterior teeth are the most affected teeth and major causes of the recession are lack of keratinized tissue, high frena attachments and shallow vestibular depth. However, free grafts frequently result in a poor aesthetic appearance due to unsatisfactory chromatic, texture, tissue integration and apical disalignment of alveolar mucosa. Therefore, partly epithelialized free gingival graft (PE-FGG), with an apical de-epithelialized portion designed to overcome some of the aesthetic problems associated with the conventional FGG. The aim of this study was to compare the RES score of the PE-FGG and conventional FGG in Miller class II and III recessions.Material and Methods: 32 patients with 32 Miller class II and III recessions in mandibular anterior teeth were chosen. Sixteen mandibular central teeth were chosen for FGG procedure and sixteen mandibular central teeth were chosen for PE-FGG procedure. All patients were periodontally healthy women.Results: All patients completed the study and attended all recall visits. The mean RES score of the FGG and PE-FGG groups were 5,25±0,85 6,56±0,72 respectively. PE-FGG gave a better RES score and gingival color (p<0.05) than FGG but full root coverage was not achieved.Conclusion: The PE-FGG procedure resulted in excellent gingival color and better mucogingival alignmenet and RES score than FGG and can be used instead.